Cellular pathology of glandular lesions and uncommon neoplasms of the cervix - McCluggage, W. Glenn (Springer London, 2014)
This book provides a comprehensive account of the cellular pathology of glandular lesions and uncommon neoplasms of the cervix and places these in a contemporary clinical context. The book features comprehensive, detailed descriptions and a consistent approach to each tumor or tumor-like condition with clear color illustrations. Cytological/histological correlation is emphasised and diagnostic pitfalls are highlighted. Cellular Pathology of Glandular Lesions and Uncommon Neoplasms of the Cervix is aimed at both trainee and consultant pathologists.